Gene expression in diabetic nephropathy - Rose, Daniela; Woude, Fokko J. van der (Current diabetes reports, 2004)
Diabetic nephropathy (DN) is a common complication of diabetes types 1 and 2. One of the hallmarks of DN is the development of mesangial expansion, which occurs through accumulation of extracellular matrix (ECM) components. Altered local gene expression of humoral factors (eg, transforming growth factor-â, connective tissue growth factor, and platelet-derived growth factor) can lead to increased production of ECM components (eg, fibronectin and collagen IV) or decreased degradation through matrix metal oproteinases (eg, MMP-1, MMP-2). In recent years, new techniques for examination of gene expression have been developed. Because of their large scale and high-throughput character, it is now possible to examine differential gene expression in a large number of samples. This paper provides an overview of techniques used and results obtained in studies of DN. Newly developed concepts of how altered gene expression may affect histomorphologic features or clinical symptoms are also discussed.
Gesehen am 27.05.2022